A comment on arguments of mental model theory of causation. Issue 3 (3rd April 2023) - Yin, Pengfei
ABSTRACT: Causation is a complex concept. No single monistic theory of causation is likely to account for it (Wolff, P. (2014). Causal pluralism and force dynamics. In B. Copley, F. Martin, & N. Duffield (Eds.), Forces in grammatical structures: Causation between linguistics and philosophy ). Nonetheless, mental model theory (MMT) claims to provide a unified account of causal representation and inference. In MMT, a singular causal claim "A caused B" has a deterministic meaning referring to three temporally ordered possibilities: A and B, not-A and B, not-A and not-B. No internal components such as mechanisms, powers, or dependencies are part of the core meaning of causal claims. It is argued that MMT's attempts to refute counterexamples to its proposals are manifestly inadequate. Theoretically, the all-encompassing ambition of MMT make it so flexible as to be trivial. Technically, the term "modulation" is an unanalyzed and self-inconsistent concept. Moreover, in many situations, mental models are redundant for causal representation and inference. MMT's monistic-deterministic view cannot capture the full complexity of causation.